Substrate stiffness-driven membrane tension modulates vesicular trafficking via caveolin-1. - Lachowski,D; Matellan,C; Gopal,S; Cortes,E; Robinson,BK; Saiani,A; Miller,AF; Stevens,MM; Del,Río Hernández AE (ACS Nano, 2022)
Liver fibrosis, a condition characterized by extensive deposition and cross-linking of extracellular matrix (ECM) proteins, is idiosyncratic in cases of chronic liver injury. The dysregulation of ECM remodeling by hepatic stellate cells (HSCs), the main mediators of fibrosis, results in an elevated ECM stiffness that drives the development of chronic liver disease such as cirrhosis and hepatocellular carcinoma. Tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) is a key element in the regulation of ECM remodeling, which modulates the degradation and turnover of ECM components. We have previously reported that a rigid, fibrotic-like substrate can impact TIMP-1 expression at the protein level in HSCs without altering its mRNA expression. While HSCs are known to be highly susceptible to mechanical stimuli, the mechanisms through which mechanical cues regulate TIMP-1 at the post-translational level remain unclear. Here, we show a mechanism of regulation of plasma membrane tension by matrix stiffness. We found that this effect is orchestrated by the β1 integrin/RhoA axis and results in elevated exocytosis and secretion of TIMP-1 in a caveolin-1- and dynamin-2-dependent manner. We then show that TIMP-1 and caveolin-1 expression increases in cirrhosis and hepatocellular carcinoma. These conditions are associated with fibrosis, and this effect can be recapitulated in 3D fibrosis models consisting of hepatic stellate cells encapsulated in a self-assembling polypeptide hydrogel. This work positions stiffness-dependent membrane tension as a key regulator of enzyme secretion and function and a potential target for therapeutic strategies that aim at modulating ECM remodeling in chronic liver disease.